Pedro Cano and the Maritime Theatre in Hadrian’s Villa (diségno, 2017)
In 1989 the Spanish artist Pedro Cano [1] designed the stage set and costumes for a performance to be held in Hadrian’s Villa in Tivoli. The play entitled Hadrian’s Memoirs: portrait of a voice [2] was based on excerpts from the novel by Marguerite Yourcenar, interpreted by actors Giorgio Albertazzi, Eric Vu An and Maria Carta, and directed by Maurizio Scaparro [3]. Cano’s very intense and meaningful painting of the Maritime Theatre in Hadrian’s Villa is part of his 160 x 100 cm series of watercolours of Greek and Roman theatres and amphitheatres.  Although the artist executed this particular painting in 2016, he had already painted the site many years earlier when he created a notebook of paintings of Hadrian’s Villa and a series of twelve aquatints in which he included not only the theatre, but also other architectures in the complex.